Biomass accumulation in a naturally regenerating lowland secondary forest and an Acacia mangium stand in Sarawak - Lim, Meng Tsai; Hamzah, Mohd Basri (Universiti Pertanian Malaysia Press, 1985)
The floristic composition and the above ground biomass of a naturally regenerating area and a three-and-a-half year-old Acacia mangium stand are compared. The naturally regenerating area averages 1.5 m in height; generally has more variety of plants and is dominated by Imperata cylindrica, Dicranopteris linearis, Pteridium sp. and Scleria sp. whereas the A. mangium stand has a top height of 15.5 m and fewer genera of plants (including cocoa). I. cylindrica and D. linearis were also found in the A. mangium stand but grew less vigorously in isolated patches. There was 6.2 t/ha of live organic matter in the naturally regenerating area and approximately 59.0 t/ha in the A. mangium stand.